ASSESSING THE IMPACT OF CLIMATE CHANGE ON SUSTAINABLE DEVELOPMENT: A COMPREHENSIVE ANALYSIS - Jobborov Azamjon Mashrabovich; Tojiboyeva Makhliyo daughter of Azamjon; Meliyev Muzaffar Saidakbarovich (Galaxy International Interdisciplinary Research Journal, 2024)
This research paper examines the multifaceted effects of climate change on sustainable development. The study explores environmental, economic and social aspects, exploring global and regional perspectives. Through rigorous analysis and empirical evidence, the paper aims to enhance our understanding of the challenges climate change poses to sustainable development, providing insights that inform effective mitigation and adaptation strategies.